Adopsi Petani Dalam Penggunaan Traktor Roda Dua Mengolah Lahan Padi Sawah Di Kecamatan Gomo Kabupaten Nias Selatan Provinsi Sumatera Utara - Dwi Febrimeli; Ameilia Zuliyanti Siregar; Terima Jaya Laia (Jurnal Sosial Ekonomi Pertanian, 2022)
This study aims to (1) analyze the level of adoption of farmers in the use of two-wheeled tractors in lowland rice cultivation in Gomo sub-district, South Nias district (2) to analyze what factors influence the level of farmer adoption in the use of two-wheeled tractors in Gomo sub-district. South Nias Regency in March to May 2021. This assessment method uses a quantitative approach to determine the level of farmer adoption in the use of two-wheel tractors in the cultivation of lowland rice using the Liker model scoring technique, and to analyze what factors influence the level of adoption of farmers in the use of two-wheeled tractors in the cultivation of rice fields using multiple linear analysis models. The results of this study are the adoption of farmers in the use of two-wheel tractors in the cultivation of lowland rice fields is classified as very high (82.94%). The factors that significantly influence the adoption of farmers in the use of two-wheeled tractors in rice field cultivation in Gomo District, South Nias Regency are income, nature of innovation, role of group leader, role of extension workers, and factors that have no effect, age, cosmopolitan , and land area.